Foreign firms' access to the Japanese market. (1st January 2014) - Bebenroth, Ralf; Kshetri, Nir; Hünerberg, Reinhard
This paper examines interrelationships among foreign firms' perceptions of market barriers related to the access, quality of inter-organisational institutions and their market commitment and performance in Japan. Our findings suggest that foreign firms that perceive a higher level of macro-level institutional barrier are likely to have an unfavourable assessment of the accessibility of the Japanese distribution system. We also found that firms with a favourable assessment of the accessibility of the Japanese distribution system are likely to develop better inter-organisational networks. Finally, our findings would suggest that firms with a higher level of commitment to and performance in Japan are characterised by a favourable assessment of the accessibility of the Japanese distribution system and better inter-organisational networks. Implications are discussed.